Extinction risks and resilience: A perspective on existential risks research with nuclear war as an exemplary threat - Johannes Kattan (Intergenerational Justice Review)
A growing awareness of potential global catastrophes has recently given increased attention to the topic of existential risks. To date, there is still very limited consensus on the definition of existential risk, the likelihood of those risks, and their ethical implications. To achieve more clarity, it is proposed here that extinction risks should be discerned more clearly from other aspects of existential risks. Nuclear war is taken as a prime example to illustrate an extinction risk and to discuss humanity’s resilience to such threats. It is concluded that it is unlikely that a nuclear war would lead to the end of the human species, despite the unprecedented damage it might cause. Further, some of the ethical aspects of longtermism and the communication of existential risks are discussed.